International students mobility: A case of Pakistan - Farrukh Nawaz Kayani; Mumtaz Ahmed; Muhammad Tahir Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
In the current century, it is becoming more and more critical and important for every individual to have a global perspective in pursuing and shaping his/her future. Through studying abroad people can realize their full potential to benefit the community and nation. International students are an important source of additional financial resources for academic institutions. The academic mobility is mainly for the rich class and it continues to be a privilege of economic elite. Since the establishment of Higher Education Commission (HEC) of Pakistan in 2002, the students from average and poor families of Pakistan have also been abroad for higher studies. The selection of these students is done via a Graduate Record Examination (GRE).Their entire expenses of the successful candidates are born by HEC, Pakistan. In this paper, we would thoroughly discuss and analyze the trends of outbound Pakistani students by taking statistical data from Higher Education Commission of Pakistan and other secondary sources. The top host countries for Pakistani students and the academic achievements of these students abroad would also be analyzed.
Keywords: 330; internationalization; student mobility; higher education; Pakistan